Design of a cyber-physical production system for semiconductor manufacturing - Sophia Keil (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Due to the highly dynamic markets, an increasing complexity, and individualization of products, efficient and robust logistical processes are difficult to achieve through the use of central planning and control approaches. The aim of the contribution is the design of a decentralized, autonomous control system for high tech production systems. An interdisciplinary perspective was adopted as methods of artificial intelligence and mechanical as well as electrical engineering were used. The results are a hardware concept for an intelligent, cyber-physical production lot and a software concept based on a hierarchical multi-agent architecture. The basic idea of autonomy and self-control is not new. It can be traced back, for example, to the ideas of 'Evolutionary Management', or cybernetics. However, for the first time this contribution shows a practical application for a complex semiconductor manufacturing system. Until now, the hard and software concepts have been implemented prototypically. A long-term integration into the existing IT landscape of a semiconductor factory is planned. A well established and functioning centralized system should be supplemented by the new decentralized system, especially in areas in which there is not yet such a high level of automated processes, e. g. in wafer test facilities.
urn:nbn:de:gbv:830-88217553; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; cyber-physical production system; multi-agent system; intelligent production lot; semiconductor manufacturing